The Influence of Service Quality on the Satisfaction Of Umrah Pilgrims in Shafwah Holidays South Tangerang - Estikowati; Yulianto, Irwan; Lasarudin, Alwin; Putri, Nabila Raisaa (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This research was conducted at Shafwah Holidays South Tangerang, especially on the effect of service quality on the satisfaction of Umrah pilgrims. Umrah is a visit to Baitullah to perform tawaf, sa'i, and shave in order to hope for the pleasure of Allah SWT. or also called Little Hajj. Service quality is a dynamic state that is closely related to products, services, human resources, as well as processes and environments that can at least meet or exceed the quality that customers expect. Consumer or customer satisfaction is a person's feeling of pleasure or disappointment that arises after comparing the performance of the estimated results (products) against the expected performance or results. Customer satisfaction can also be achieved with good and satisfactory service quality. In order to get a satisfactory assessment from customers or good service quality, there are five main dimensions or indicators that need to be considered, namely: (1) Reliability, (2) Assurance, (3) Tangible, (4) Empathy, and (5) Responsiveness. The method used in this study is a quantitative